Erucic acid from Isatis indigotica Fort. suppresses influenza A virus replication and inflammation in vitro and in vivo through modulation of NF-κB and p38 MAPK pathway - Xiaoli Liang; Yuan Huang; Xiping Pan; Yanbing Hao; Xiaowei Chen; Haiming Jiang; Jing Li; Beixian Zhou; Zifeng Yang (Elsevier, 2020)
Isatis indigotica Fort. (Ban-Lan-Gen) is an herbal medicine prescribed for influenza treatment. However, its active components and mode of action remain mostly unknown. In the present study, erucic acid was isolated from Isatis indigotica Fort., and subsequently its underlying mechanism against influenza A virus (IAV) infection was investigated in vitro and in vivo. Our results demonstrated that erucic acid exhibited broad-spectrum antiviral activity against IAV resulting from reduction of viral polymerase transcription activity. Erucic acid was found to exert inhibitory effects on IAV or viral (v) RNA-induced pro-inflammatory mediators as well as interferons (IFNs). The molecular mechanism by which erucic acid with antiviral and anti-inflammatory properties was attributed to inactivation of NF-κB and p38 MAPK signaling. Furthermore, the NF-κB and p38 MAPK inhibitory effect of erucic acid led to diminishing the transcriptional activity of interferon-stimulated gene factor 3 (ISGF-3), and thereby reducing IAV-triggered pro-inflammatory response amplification in IFN-β-sensitized cells. Additionally, IAV- or vRNA-triggered apoptosis of alveolar epithelial A549 cells was prevented by erucic acid. In vivo, erucic acid administration consistently displayed decreased lung viral load and viral antigens expression. Meanwhile, erucic acid markedly reduced CD8+ cytotoxic T lymphocyte (CTL) recruitment, pro-apoptotic signaling, hyperactivity of multiple signaling pathways, and exacerbated immune inflammation in the lung, which resulted in decreased lung injury and mortality in mice with a mouse-adapted A/FM/1/47-MA(H1N1) strain infection. Our findings provided a mechanistic basis for the action of erucic acid against IAV-mediated inflammation and injury, suggesting that erucic acid may have a therapeutic potential in the treatment of influenza. Keywords: Influenza A virus, Isatis indigotica Fort., Erucic acid, Antiviral, Anti-inflammatory, NF-κB, p38 MAPK, Lung injury